2020
DOI: 10.1016/j.jsxm.2019.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Pedophilic Sexual Interest

Abstract: Introduction Pedophilic sexual interest is an important risk factor in sexual offender recidivism and remains a key component in the clinical assessment of child sexual offenders and people diagnosed with pedophilia. Despite concerns about the absence of universally accepted standardized clinical assessment methods, there are a number of established techniques aimed at assessing people with sexual interest in children. Aim To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…However, Babchishin et al 19 found from a large sample that over 80% of PCSOs against children were unable to successfully inhibit their sexual arousal to children when instructed to do so. Some laboratories check examinees' attention to the stimuli by asking them to describe it 20 or by videoing their upper body. 14 Third, the specificity of phallometry is an important consideration owing to the potential implications of incorrectly identifying an examinee with a PSI.…”
Section: Limitations To Phallometry Might Be Divided Into Technical Factors and Societal Factors Includingmentioning
confidence: 99%
“…However, Babchishin et al 19 found from a large sample that over 80% of PCSOs against children were unable to successfully inhibit their sexual arousal to children when instructed to do so. Some laboratories check examinees' attention to the stimuli by asking them to describe it 20 or by videoing their upper body. 14 Third, the specificity of phallometry is an important consideration owing to the potential implications of incorrectly identifying an examinee with a PSI.…”
Section: Limitations To Phallometry Might Be Divided Into Technical Factors and Societal Factors Includingmentioning
confidence: 99%
“…Deviant response profiles are not an indication of guilt for the commission of a past offense (Carvalho et al, 2020;Demidova et al, 2019;Fedoroff et al, 2009;. PPG does not act as a "lie detector" and should never be used when determining culpability for a particular offense.…”
Section: Ppg Use In Legal Casesmentioning
confidence: 99%
“…Regardless of research that has found an association between deviant arousal patterns, as measured by PPG, and an individual's risk of recidivism (Hanson & Morton‐Bourgon, , , , ), PPG cannot act as a determination of guilt or innocence for a person accused of a sexual offense. Deviant response profiles are not an indication of guilt for the commission of a past offense (Carvalho et al, ; Demidova et al, ; Fedoroff et al, ; Murphy, Ranger, Stewart, et al, ). PPG does not act as a “lie detector” and should never be used when determining culpability for a particular offense.…”
Section: Ppg Use In Legal Casesmentioning
confidence: 99%
See 2 more Smart Citations